Antioxidant, Anti-Aging and Antibacterial Activity from Dewa Leaves Ethanolic Extract (Gynura japonica (Thunb.) Juel) - Fatmawati, Umi; Zienitha, Anggie Meilinda; Anggraini, Meisi; Rosita, Lisa; Indrowati, Meti; Harlita, Harlita; Santosa, Slamet; Permatasari, Vera; Primahana, Gian; Yati, Indri; Prastya, Muhamad Eka (Molekul, 2025)
ABSTRACT. Due to their phytochemical constituents, Dewa leaves (Gynura japonica (Thunb.) Juel.) are often used in traditional medicinal herbs. However, in vitro and in vivo of antioxidative and anti-aging studies of Dewa leaves on yeast as a eukaryotic cell model have not been widely carried out. This study aims to determine the antioxidant, anti-aging, and antibacterial activities derived from G. japonica leaves extract. Extraction was conducted using 70% and 96% ethanol solvents, total phenolic content (TPC) was assayed using Folin-Ciocalteu method, flavonoid contents (TFC) was assayed using aluminum chloride method, antioxidant activity was tested using DPPH (1,1-diphenyl-2-picrylhydrazyl) and ABTS (2,2-azinobis-3-Ethylbenzothiazoline)-6-sulfonic acid) radicals. Subsequently, an anti-aging activity test was performed on the yeast Saccharomyces cerevisiae as a model organism following antibacterial activity. The antibacterial activity test was carried out using well diffusion agar, and the Minimal Inhibitory Concentration (MIC) was determined using the microplate method. We obtained that G. japonica leaves extracted from 70% and 96% methanol solvents, have TPC of 13.14 and 22.11 mg GAE/gr extract, and TFC of 8.04 and 14.09 mg QE/gr extract, respectively. As for DPPH and ABTS antioxidant activity, D70 showed the best activity with IC50 values of 1411.36±56.35 µg/mL and 2516.10±18.77 µg/mL, respectively. The anti-aging test showed that both 70% and 96% ethanol extracts were able to maintain the yeast cell viability under H2O2 oxidative stress. Further, 70% and 96% ethanol extract also showed antibacterial activity at the best value against Staphylococcus aureus with a MIC value of 390.62 µg/mL, it means that Gynura leaves extract has a potency as antibacterial agent. The results of this study indicate that the ethanol extract of G. japonica leaves can be developed for further investigation as an antioxidant and antibacterial therapeutic agent. Keywords: Anti-aging, antibacterial, antioxidant, Gynura japonica, Saccharomyces cerevisiae